Native C3 is activated without proteolytic cleavage by transformation to C3(H2O) on phospholipid-scrambled cell membranes - Eikrem, David; Manivel, Vivek A.; Whittaker, Jacob; Hamad, Osama A.; Mohlin, Camilla; Adler, Anna; Dührkop, Claudia; Ebert, Roland; Teramura, Yuji; Ekdahl, Kristina N.; Fromell, Karin; Nilsson, Bo (Frontiers in Immunology, 2025)
Tick-over of C3 to fluid-phase C3(H2O) is considered the initiator of the alternative pathway by mediating random depositing of C3b on target surfaces. This slow mechanism does not explain the specificity and rapid activation of the alternative pathway in vivo. In thromboinflammatory disorders, C3(H2O) also exists in a bound form on activated platelets and endothelial cells. Here, we investigate this binding mechanism. C3, C3b, and C3(H2O) were exposed to activated platelets expressing phospholipid-scrambled membranes. Native C3 demonstrated the highest binding to activated platelets compared to C3b and soluble C3(H2O) and revealed the most efficient convertase (C3bBb) formation. The specific binding of annexin V to phospholipid-scrambled membranes, inhibited C3 binding to activated platelets, and to apoptotic PMN and endothelial cells, while properdin enhanced both binding and convertase generation. Model liposomes exposing phosphatidylserine, bound native C3 in a cholesterol-dependent manner. Neoepitopes and cryo-TEM, showed that the conformation of liposome-bound C3 resembles C3(H2O) and quartz crystal microbalance with dissipation monitoring (QCM-D) its ability to form C3bBb convertases. Thus, native C3 transforms into C3(H2O) by binding to phospholipid-scrambled membranes, identifying native C3 without proteolytic cleavage, as a direct recognition molecule of altered self (in this case exposure of phospholipids that are not found on the surface of native, healthy, cells) acting as a key initiator of the alternative pathway and a mediator of phagocytosis in thromboinflammatory pathologies.